Hubungan Pengetahuan dan Sikap dengan Perilaku Merokok pada Remaja di SMP PGRI Kota Sorong: Hubungan Pengetahuan Dan Sikap Dengan Perilaku Merokok Pada Remaja Di SMP PGRI Kota Sorong - simon, merlis; R, Astuti; Limbu, Desby Sutria (Jurnal Kesehatan, 2023)
Smoking is a behavior that has become a habit in society and especially teenagers. This behavior is carried out by teenagers with the aim of finding peace because smoking can reduce tension and make it easier to concentrate. The Global Adult Tobacco Prevalence Survey (GATS) states that Indonesia is the country with the highest number of teenage smokers in the world with the number of smokers aged ≥ 15 years is 38%, with men at 67% and in 2018 at 91%. The aim of this research was to determine the relationship between knowledge and attitudes towards smoking behavior among adolescents in one of the junior high schools in Sorong City. This type of research is quantitative research with a cross sectional design. The test used was Chi-square test. The instrument used was the Global Youth Tobacco survey research questionnaire. The location of this research was one of the junior high schools in Sorong City, and the time of the research was July 2023. The population in this research was 117 teenagers, while the number of samples was 90 respondents, that was taken using the Slovin formula. The results of the research showed that there was a relationship between knowledge and attitudes towards smoking behavior in adolescents with a significance value of p=0.000 (<α=0.05). The conclusion is that there is a relationship between knowledge and attitudes towards smoking behavior among teenagers in one of the junior high schools in Sorong City. It is suggested for educational institutions to become one of the institutions that can help in providing information about smoking behavior which can endanger the health of teenagers.